Analysis of Rice Farmers' Decisions in Selling Production Results in East OKU Regency - Slamet; Munajat, Munajat; Oktarina, Yetti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
This study aims to analyze the key factors influencing rice farmers' decisions to sell their production in East OKU Regency. Methodology: The research was conducted in three districts—East Buay Madang, Buay Madang, and Madang Suku I—selected purposively based on their large rice production areas. Using a case study approach, data were collected from 118 respondents through multi-stage random sampling. Logit regression analysis was employed to identify the factors affecting farmers' sales decisions. The results indicate that production volume, urgent financial needs, middlemen involvement, and milling costs significantly influence farmers' decisions to sell their rice in the form of grain. Meanwhile, labor availability does not have a significant impact. The findings highlight that most farmers prefer selling unprocessed grain due to immediate financial needs and dependency on middlemen, despite the lower prices compared to selling processed rice.: To enhance farmers' income and economic resilience, it is essential to stabilize grain prices, reduce milling costs, and provide better financial support and market access. Encouraging more farmers to process their grain into rice before selling could lead to greater profitability and reduced reliance on middlemen.